New molecular data help clarify the taxonomy of central European avian dicrocoeliidae Looss, 1899 (Trematoda: Plagiorchiida) - Heneberg, Petr; Sitko, Jiljí; Casero, María; Rząd, Izabella (International journal for parasitology. Parasites and wildlife, 2023)
Avian Dicrocoeliidae are difficult to identify, even in their adult stages. Molecular analyses have been conducted for only a few species, complicating the accurate identification of juvenile stages. The taxonomy of the family is unresolved, and the status of many dicrocoeliid species is uncertain. Sequences of nuclear and mitochondrial DNA loci of Central European avian Dicrocoeliidae were generated and analyzed. These included representatives of the genera Lyperosomum, Platynosomum, Stromitrema, Brachylecithum, Brachydistomum, and Lutztrema. All the sequences were obtained from morphologically identified adult specimens of dicrocoeliids isolated from avian hosts. Molecular support was obtained to validate Lyperosomum turdia, confirm the rejection of Lyperosomum dujardini and Lyperosomum alagesi, and resurrect Lyperosomum longicauda and Lyperosomum collurionis. The identity of European Platynosomum illiciens from avian hosts with American vouchers of the same species from avian and mammalian hosts was confirmed. Brachylecithum fringillae is not considered valid; the individuals that matched its diagnosis were subadult Brachydistomum ventricosum. Descriptions and comparative data for five new species are provided. These are Lyperosomum hirundinis sp. n., Lyperosomum tenori sp. n., Lyperosomum atricapillae sp. n., Stromitrema acrocephali sp. n., and Lutztrema atricapillae sp. n.. Based on the molecular data, suggestions are provided regarding the validity of dicrocoeliid species that parasitize Central European birds. Further research should address the polyphyletic status of Brachylecithum.
Keywords: Bird; Bile duct; Platyhelminthes; Gall bladder; Dicrocoeliidae; Cryptic species